A Domino Approach for the Synthesis of 4-Carboxamide Oxazolines from Azirines - Nikbakht, Ali; Mohammadi, Fariba; Mousavi, Mohammad Sadeq; Amiri, Kamran; Balalaie, Saeed; Rominger, Frank; Bijanzadeh, Hamid Reza (Synthesis, 2021)
A regio- and diastereoselective ring-expansion reaction of N-acylaziridines is described for the synthesis of 4-carboxamide oxazolines using InCl3. A domino Ugi–Joullié/ring-expansion reaction of arylphenylazirines, isocyanides, and carboxylic acids leads to the target products through the N-acylaziridine intermediates in the presence of the indium catalyst. The oxazolines were synthesized in moderate to excellent yields with high atom economy and high bond-forming efficiency under mild reaction conditions.
Keywords: domino approach; 4-carboxamide oxazolines; azirines